Qur'anic Perspectives On Knowledge And Knowledge Seekers: Perspektif Al-Quran Tentang Ilmu Dan Penuntut Ilmu - Huriadi, Mohammad Dera; Ahmad, Lalu Turjiman; Hamim, Nur (PT. Student Rihlah Indonesia, 2024)
The Quranic perspective on knowledge and knowledge claimants is very detailed, where many Quranic verses speak of knowledge and also tell about knowledge claimants, both those who have status as scholars and prophets. The purpose of this research is to know and understand the Quranic perspective on science and the benefits of science. In this research, data collection is obtained through a literature study approach by collecting primary sources in the form of original writings of scholars and secondary sources in the form of dictionaries or other people's research results so that in the future it can become a reference in state Islamic universities in Indonesia. Based on the results of the study, Science is a gift from Allah SWT to His servants, a servant can bind all knowledge, be it religious knowledge or the universe with writing, because Allah tells us to read his verses, be it verses related to religious laws, or with existing science. Being a seeker of knowledge and an expert in knowledge is the highest degree of a believer, because it is clear the difference between a believer with knowledge and a believer without knowledge.